2017
DOI: 10.1002/chem.201700171
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of 2,3‐Dihydrobenzofurans by a [4+1] Annulation Between Ammonium Ylides and In Situ Generated o‐Quinone Methides

Abstract: A highly enantio‐ and diastereoselective [4+1] annulation between in situ generated ammonium ylides and o‐quinone methides for the synthesis of a variety of 2,3‐dihydrobenzofurans has been developed. The key factors controlling the reactivity and stereoselectivity were systematically investigated by experimental and computational means and the energy profiles obtained provide a deeper insight into the mechanistic details of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…One year later Waser's group also established similar kind of asymmetric [4+1] cyclization reaction of ammonium ylides 152 and in situ generated o ‐quinone methides ( o ‐QMs) from 151 for the synthesis of 2,3‐dihydrobenzofurans . In this protocol, initially, the cinchona alkaloids 35 reacted with ammonium salts 152 which allows the generation of in situ chiral ammonium ylide 35 which participated in the [4+1] cyclization reaction with o ‐QMs to obtain product 153 with control of both the relative and the absolute configuration (Scheme ).…”
Section: Synthesis Of Dihydrobenzofuransmentioning
confidence: 99%
“…One year later Waser's group also established similar kind of asymmetric [4+1] cyclization reaction of ammonium ylides 152 and in situ generated o ‐quinone methides ( o ‐QMs) from 151 for the synthesis of 2,3‐dihydrobenzofurans . In this protocol, initially, the cinchona alkaloids 35 reacted with ammonium salts 152 which allows the generation of in situ chiral ammonium ylide 35 which participated in the [4+1] cyclization reaction with o ‐QMs to obtain product 153 with control of both the relative and the absolute configuration (Scheme ).…”
Section: Synthesis Of Dihydrobenzofuransmentioning
confidence: 99%
“…The syntheses of dihydrobenzofurans 88 by the addition of onium ylides to in situ generated o -quinone methides 89 have recently received much attention. [57–60] Approximately a year ago, we reported the first highly asymmetric synthesis of dihydrobenzofurans 88 by using a chiral ammonium ylide strategy. [57] After screening different chiral ammonium salts, we realized that quinidine-based salts 92 serve to achieve high enantio- and diastereoselectivities for this formal [4+1] annulation reaction, in which quinone methide 89 and ylide 91 are both generated in situ under basic reaction conditions (Scheme 24A).…”
Section: Formal [4+1] Cyclizationsmentioning
confidence: 99%
“…Scheme 23), as the formation of the ammonium salt turned out to be slow under the reaction conditions relative to the decomposition of 90 . [57]…”
Section: Formal [4+1] Cyclizationsmentioning
confidence: 99%
“…Interestingly however, their applicability for asymmetric [4+1]‐cyclizations to access dihydrobenzofurans 1 has so far been rather limited, with highly asymmetric protocols still being rare (Scheme B) . Two years ago we reported the first highly enantioselective synthesis of compounds 1 by reacting preformed chiral ammonium ylides with in situ formed o ‐QMs 2 . More recently we found that the highly functionalized allenoates 4 can undergo a very unique (and up to then unprecedented) formal [4+1]‐cyclization with acceptors 2 in the presence of a stoichiometric amount of PPh 3 (Scheme C) .…”
Section: Introductionmentioning
confidence: 99%